Problem-based learning on students' English learning interests - Siti Syafi’atul Qomariyah; I Made Permadi Utama (International Journal of Language Teaching and Education, 2021)
This study was conducted to find out how Problem Based Learning (PBL) affects students' English learning interests. The questionnaire is used as an instrument. The result of implementing the Problem Based Learning (PBL) method was that students felt enjoy and more interested. The students could develop their brainstorming when the teacher provided a problem to discuss with their group. They also created some ideas for solving their problem. Some students also provide their daily problems and make the classroom/discussion situation life. Based on data analysis showed that computing of the t-test was significant 0.000. It means that applying Problem Based learning (PBLaffects students' learning interests. So, this method can be used as one of the alternative ways of teaching-learning to develop students' learning interests.